2010
DOI: 10.1159/000320984
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Erosion in Dietary Acids: Inhibition by Food Proteins in vitro

Abstract: The aim of this study was to investigate the effects of two common food proteins on human enamel erosion in vitro. Erosion was measured by non-contact profilometry in citric, malic and lactic acids at pH 2.8, 3.2 and 3.8 and five commercially available soft drinks, in the presence of a salivary pellicle. Whole milk casein or hen egg ovalbumin was added to the acid solutions and drinks at 0.2% w/v, and the effect on erosion was determined by comparison with the corresponding solution without protein. Casein sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 35 publications
0
35
0
12
Order By: Relevance
“…From a different perspective, the addition of casein to acid solutions and commercial soft drinks was able to considerably reduce in vitro enamel erosion [Hemingway et al, 2010]. The authors speculated that the casein added to the acid/soft drink can also interact with the AEP or with the enamel surface itself, resulting in a casein-rich film that may enhance protection against erosion [Hemingway et al, 2010].…”
Section: Products Containing Other Proteins or Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…From a different perspective, the addition of casein to acid solutions and commercial soft drinks was able to considerably reduce in vitro enamel erosion [Hemingway et al, 2010]. The authors speculated that the casein added to the acid/soft drink can also interact with the AEP or with the enamel surface itself, resulting in a casein-rich film that may enhance protection against erosion [Hemingway et al, 2010].…”
Section: Products Containing Other Proteins or Polymersmentioning
confidence: 99%
“…The authors speculated that the casein added to the acid/soft drink can also interact with the AEP or with the enamel surface itself, resulting in a casein-rich film that may enhance protection against erosion [Hemingway et al, 2010]. Likewise, when casein was added to a dentifrice together with other proteins, Jager et al [2013] reported promising results for the prevention of erosion, but further research is still necessary to understand how and whether these products are able to prevent erosion in vivo.…”
Section: Products Containing Other Proteins or Polymersmentioning
confidence: 99%
“…Several studies have demonstrated the antierosive potential of tannin (34,35). It is possible that tannin inhibits de-mineralization through interaction with the organic matrix of enamel.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also shown that the addition of food proteins (casein and ovalbumin) reduced enamel erosion [6], probably due to adsorption of protein to the hydroxyapatite surface [7]. The proteins might form a semi-permeable barrier, hindering transport of protons towards the hydroxyapatite crystal surface and/or calcium and phosphate ions away from the surface [8].…”
Section: Introductionmentioning
confidence: 99%